Identifikasi Sektor Ekonomi Potensial Untuk Mendukung Optimalisasi Pendapatan Daerah Kabupaten Karo - Subakti, Sinarta Putra P.; Sugiri, Dani (Jurnal Ekonomi-Qu, 2024)
This research aims to identify the potential economic sectors for optimizing regional income in Karo Regency. The research utilizes time series data of Gross Regional Domestic Product (GRDP) based on Constant Prices by the Central Statistics Agency (BPS). The Location Quotient (LQ) analysis tool is employed to determine the basic and prospective sectors. The research findings indicate that Karo Regency has four potential economic sectors: Accommodation and Food Services; Public Administration, Defense, and Mandatory Social Security; Education Services; and Other Services. The Accommodation and Food Services sector can directly enhance the regional income of Karo Regency through revenue from Hotel Tax, Restaurant Tax, and Entertainment Tax, closely related to the tourism potential of Karo Regency. Additionally, there is a non-basic but prospective sector linked to Street Lighting Tax revenue, which is the Electricity and Gas Supply sector. Optimization of this sector can be achieved by harnessing geothermal energy for Geothermal Power Plant (PLTP).